2004
DOI: 10.1111/j.0013-8703.2004.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of alate aphids to green targets on coloured backgrounds

Abstract: To study the effect of background colour on aphid landing on green targets (water pan traps), two field experiments were set up in Hessen, Germany, in 2003. Traps were put onto coloured plastic sheets (13 colours, straw mulch, transparent foil, and uncovered soil, Experiment 1). In Experiment 2, green water pans were again put on coloured plastic sheets (red, white, green, and yellow), and the sheets were either sprayed with insect glue or not. Backgrounds and traps were spectrally characterised with a field r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 39 publications
3
45
1
3
Order By: Relevance
“…The attractiveness of black and straw mulches for Aphis spp. was also reported by Döring et al (2004). Furthermore, the attractiveness of straw mulch for M. persicae was observed at Pula in 2008 at a time close to the aphid population maximum, whereas the attractiveness of bare soil was noted during the period of aphid population decrease.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The attractiveness of black and straw mulches for Aphis spp. was also reported by Döring et al (2004). Furthermore, the attractiveness of straw mulch for M. persicae was observed at Pula in 2008 at a time close to the aphid population maximum, whereas the attractiveness of bare soil was noted during the period of aphid population decrease.…”
Section: Discussionsupporting
confidence: 70%
“…During the season of 2011, two assessments at Pula demonstrated the attractiveness of black PE mulch to aphid populations. According to Döring et al (2004), high numbers of winged aphids were captured in traps on dark backgrounds (black and dark green). While studying the effect of coloured mulches on pest populations, Farias-Larios & Orozco-Santos (1997) found that aphids were most numerous on bare soil and black mulch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third strategy affected by the knowledge on aphid colour responses is the use of reflective mulches, although non-visual factors may also play a role in the effects observed (Dö ring et al 2004). In the investigations on the use of mulch for protection of plants from virus diseases, three features were often stated: (1) The higher the percentage of soil covered with mulch the higher the efficiency (e.g., Adlerz and Everett 1968;Lehmhus 2001); (2) The efficiency of the mulch decreases over the growing season along with the increasing canopy of the plant (e.g., Brust 2000); (3) The comparably high costs of mulching are only economically justified in high value crops or when severe losses occur regularly due to virus diseases (e.g., Brust 2000).…”
Section: Agricultural Implications: Optimisation Of Aphid Monitoring mentioning
confidence: 99%